2020
DOI: 10.1039/d0fo00007h
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect ofLactobacillus plantarum-12 on DSS-induced murine colitis

Abstract: Lactobacillus plantarum-12 can relieve colitis, and the results have some practical value in applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 54 publications
4
36
0
Order By: Relevance
“…Chen et al demonstrated that B. breve could alleviate DSS-induced colitis by regulating the gut microbiota. In the current study, DSS administration increased the Simpson index compared to that in the NC group, which is consistent with the results of sun et al [60]. However, B. lactis XLTG11 supplementation reversed this trend.…”
Section: Discussionsupporting
confidence: 93%
“…Chen et al demonstrated that B. breve could alleviate DSS-induced colitis by regulating the gut microbiota. In the current study, DSS administration increased the Simpson index compared to that in the NC group, which is consistent with the results of sun et al [60]. However, B. lactis XLTG11 supplementation reversed this trend.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the abundance of Firmicutes increased significantly in the MDG group compared with the NC group. L. plantarum 12 increased the relative abundance of Firmicutes (Sun et al 2020), which is similar to our result. Contrary to our results, a strain of L. plantarum decreased the abundance of Firmicutes (Zhang et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, studies have shown that another strain of Lactobacillus plantarum L15 can also regulate the intestinal flora and alleviate colitis (Yu et al., 2020). Similar to the above studies, animal experiments have further proved that the intake of beneficial microorganisms can improve immunity, enhance intestinal barrier function, restore intestinal flora, play a role in reducing inflammation, and inhibit DSS induced colitis (Sun et al., 2020). In this study, LP‐YS3 also showed a good anti‐inflammatory effect, which was similar to the anti‐inflammatory effect of Lactobacillus plantarum in the above studies, and played a regulatory role in DSS colitis.…”
Section: Discussionmentioning
confidence: 79%